Lack of Tissue Virological Response as a Predictor of Relapse in Chronic Hepatitis D after Completion Bulevirtide Therapy - P. O. Bogomolov; N. A. Shub; N. A. Gasilova; A. A. Belyakova; T. G. Lidzhieva; E. A. Kondrasheva; N. A. Barsukova; M. V. Arapova; E. A. Isaeva; S. V. Koblov; M. V. Kalashnikov; O. S. Kuzymina; et al. (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2024)
Aim: to evaluate the significance of a positive polymerase chain reaction result for hepatitis D virus RNA (HDV RNA) in liver biopsy specimens of patients with chronic hepatitis D (CHD) after completion of antiviral therapy (AVT) as a predictor of infection relapse.Materials and methods. The study included 21 patients with CHD who received combined AVT with peginterferon alpha and bulevirtide for 48 weeks, followed by bulevirtide monotherapy for 48–96 weeks, making the total duration of antiviral therapy 96–144 weeks. In all patients HDV RNA became undetectable in serum 24–96 weeks from the start of treatment, with aviremia maintained for at least 48 weeks until the end of AVT. At the end of treatment, all patients underwent liver biopsy to detect HDV RNA in liver tissue.Results. Out of 21 patients with sustained complete virological response (negative polymerase chain reaction result for HDV RNA in serum), 8 (38 %) had HDV RNA detected in liver tissue, indicating that a tissue virological response was not achieved. All 8 patients experienced a relapse of CHD within 24 weeks after discontinuing AVT.Conclusions. In patients with chronic hepatitis D who have achieved a complete virological response in serum, the absence of a virological response in liver tissue (detection of HDV RNA in liver biopsy) is a predictor of relapse, providing a rationale for the continuation of antiviral therapy.